Comparison of temperature change among different adhesive resin cement during polymerization process - Murat Alkurt; Zeynep Yesil Duymus; Mustafa Gundogdu; Muhammet Karadas (Wolters Kluwer Medknow Publications, 2017)
Purpose: The aim of this study was to assess the intra-pulpal temperature changes in adhesive resin cements during polymerization. Materials and Methods: Dentin surface was prepared with extracted human mandibular third molars. Adhesive resin cements (Panavia F 2.0, Panavia SA, and RelyX U200) were applied to the dentin surface and polymerized under IPS e.max Press restoration. K-type thermocouple wire was positioned in the pulpal chamber to measure temperature change (n = 7). The temperature data were recorded (0.0001 sensible) and stored on a computer every 0.1 second for sixteen minutes. Differences between the baseline temperature and temperatures of various time points (2, 4, 6, 8, 10, 12, 14, and 16 minute) were determined and mean temperature changes were calculated. At various time intervals, the differences in temperature values among the adhesive resin cements were analyzed by two-way ANOVA and post-hoc Tukey honestly test (α = 0.05). Results: Significant differences were found among the time points and resin cements (P < 0.05). Temperature values of the Pan SA group were significantly higher than Pan F and RelyX (P < 0.05). Conclusion: Result of the study on self-adhesive and self-etch adhesive resin cements exhibited a safety intra-pulpal temperature change.